From democratic to authoritarian populism: Comparing pre- and post-2010 Hungarian pension policies - Zoltán Ádám; András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2017)
In this paper, we analyze Hungarian pension policies between 1998 and 2017, comparing the pre- and post-2010 periods. Before 2010, Hungary was a liberal democracy dominated by populist economic policies. We call this the period of democratic populism. After 2010, with center-right but illiberal Fidesz having gained a two-third supermajority of parliamentary seats and altered the entire constitutional system, a period of authoritarian populism began. Based on policy preferences and ideological orientation, one would expect the pension system to have become more stable, predictable and financially more sustainable but probably less redistributive after 2010. Yet, this is not exactly what we found by examining empirical data: whereas the transparent defined contribution element had been eliminated with the nationalization of mandatory private pension funds and redistribution toward the poor has indeed been curtailed, the pension system has hardly become more stable and sustainable after 2010. Our analyses are based on five dimensions of pension policies: (a) Creating and then renationalizing of the mandatory private pillar. (b) The tension between raising normal retirement age and stagnating effective retirement age (lack of strong benefit reduction for early retirement until 2009, introduction of Females40, and elimination of early retirement after 2010). (c) The chaotic practice of pension indexation during the whole period. (d) The polarizing impact of the elimination of progression in calculating benefits and progressivity in the personal income tax. (e) The arbitrary rise and reduction of contribution rates.
Keywords: H55; H63; 330; public pension systems; private pension systems; contributive systems; redistribution; pension policy; populism